Blockchain Based De-Duplication Analysis of Cloud Data with Data Integrity using Policy Based Encryption Technique in Cloud Storage - V. S., Badari Narayan; Kumar Bhagat, Akash; C., Chethan; Sulaiman Alfurhood, Badria; Pratap Singh, Aditya; T. R., Mahesh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Cloud computing is one of developing areas of innovation, which permits capacity, access of information, programs, and ir execution over web while supplying an assortment of data relevant administrations. With cloud data administrations, it is fundamental for data must be kept safely and to be circulated securely throughout various clients. This research propose novel technique in cloud data based de-duplication analysis and data integrity by policy based encryption in cloud storage. Here cloud based data analysis and storage analysis has been carried out. data analysis for de-duplication is carried out using blockchain technique and data integrity is carried out using policy based encryption. experimental analysis shows parametric analysis in terms of data integrity, storage analysis, throughput, end-end delay and packet delivery ratio.